Utilization of Computer-Based Testing Technology to Optimize Cognitive-Based Assessment Literacy in the Learning of Islamic Elementary School Students - Cahyaningsih, Esty; Shaleh, Shaleh; Fitriyanti, Ade (Journal of Integrated Elementary Education, 2024)
The focus of 21st-century learning is on developing students' critical thinking, real-world application of knowledge, mastery of information technology, communication, and collaboration skills. Therefore, it is important to integrate information technology into the learning process and assessment of learning outcomes. This research aims to explore how Computer-Based Testing (CBT) can enhance the quality of cognitive assessment procedures based on literacy and improve learning evaluations for students at Islamic Elementary School. This study adopted a qualitative case study design and was conducted at Islamic Elementary School Al Wathoniyah 10 East Jakarta in the second semester of the 2023/2024 academic year. The researcher used interviews, observations, and documentation as data collection methods. The findings of this research show that literacy-based cognitive assessment using CBT can optimize the quality of learning evaluation. Teachers and students are accustomed to using information and communication technology devices in learning activities. There are five stages of the procedure in literacy-based cognitive assessment using CBT to optimize the quality of learning evaluation, including the planning stage, item question development stage, validation stage, implementation stage, and evaluation stage. The investigative conducting procedure truly optimizes the quality of learning evaluation. Islamic Elementary School Al Wathoniyah 10 utilizes CBT, which has literacy-based characteristics. CBT used in learning evaluation is equipped with meaningful stimuli and various forms of questions. The questions in CBT are made as similar as possible to the national assessment questions. The educational report results in the 2023 national assessment, especially in the cognitive domain, have shown improvement. The literacy and numeracy skills of students at Islamic Elementary School Al Wathoniyah 10 have achieved good and moderate results. Both have obtained top rankings nationally.